Design and development of optical filter for biosensor - Lee, Puay Yong. (2010)
This report describes the design and development of Optical filters to be used on a Biosensor for biochemical analysis of the biological fluids in clinical diagnostics. Usually the biochemical analysis in biological fluid is carried out by optical absorption based on colorimetric detection. Hence an optical filter is used on the Biosensor, as it can selectively transmits light having certain properties (often, a particular range of wavelengths, that is, range of colors of light), while blocking the remainder which can use for accurate biochemical analysis. The optical filters were designed based on Fabry-Perot resonator formed using alternating high-low (Titanium Dioxide-Silicon Dioxide) thin films stack (with optical thickness in the range of nano-meters), and developed using electron beam evaporation technique. Material characterization using ellipsometry measurement has been done to determine the respective as-deposited material optical constants to be used in this optical filter research project. The optical constants determined from optical models were 1.459 and 2.355 for SiO2 and TiO2 at wavelength 550nm respectively. In the design and simulation phase, a comprehensive and systematic study on the potential advantages of using a double Fabry-Perot cavity designs over single Fabry-Perot cavity design were carried out. This study has shown that an optical filter performance of having a highly selective bandpass spectrum with peak transmittance >80% and full-wave-half-maximum (FWHM) bandwidth of less than 20nm can be achieved. In addition, the study also showed that double Fabry-Perot cavity designs is capable of achieving better or similar performance achieved when using single cavity designs with enhancement on the flexibility in designing and potentially lowering the numbers of layers which in turn facilitates fabrication process. Therefore in this research project, double cavities designs were fabricated and detailed further analyses on the experimental results of the optical filters samples were also covered in this research project.